Elevating the role and professional contributions of the neonatal dietitian for the future: insights from the experts themselves - Abel, Deborah M.; Gatto, Alayne M.; Fowler, Jennifer O.; Valentine, Christina J. (Frontiers in Pediatrics, 2025)
BackgroundThe neonatal registered dietitian nutritionist plays a crucial role in the care of premature and critically ill infants in the neonatal intensive care unit. Critical care success with such vulnerable patients requires expertise in patient-centered care, multidisciplinary collaboration, and adaptive clinical problem-solving. This research aimed to identify the needs, engagement levels, and expertise of the neonatal registered dietitian nutritionist while also providing insights into their job satisfaction and career longevity.MethodsThis was a cross-sectional examination using a national, online, IRB-approved survey completed by current and former neonatal practicing dietitians. In addition to descriptive statistics, the Chi-Squared test and Fisher's Exact test were used for categorical statistical analysis.Results253 current (n = 206) and former (n = 47) participants completed the online questionnaire. Before role as a neonatal registered dietitian nutritionist, 210 respondents, 84 (40%) reported having pediatric clinical experience, 94 (44%) had clinical pediatric dietetic intern experience, 21 (10%) had previously worked as a community-based pediatric nutritionist, 15 (7.1%) had specialized pediatric certification or fellowship, and 12 (5.7%) had no prior experience. Of 163 respondents, 83 (50.9%) reported receiving financial support or reimbursement for additional neonatal training. Respondents who felt valued as team members planned to stay in the neonatal registered dietitian nutritionist role for more than 5 years (p > 0.0046). Additionally, they reported having acknowledgement and appreciation (64.4%), motivation (54.1%), and opportunities for advancement (22.9%).ConclusionNeonatal registered dietitian nutritionists do not have a clear competency roadmap, nor a defined career development track. In addition, financial support or reimbursement for continuing education is not consistently an employee benefit, which may play a key role in job satisfaction and retention. This data provides valuable insights for not only managers of dietitians but also professional societies and hospital administration to build career and employee retention opportunities, and to ensure safe patient care for the smallest hospital patients.Clinical Trial RegistrationClinicalTrials.gov, identifier NCT06771778.